Cluster analysis reveals latent structure in stakeholder interests relevant to the management of Blueskin Bay estuary, Otago, Aotearoa New Zealand. Issue 3 (3rd July 2022) - Langhans, Simone D.; Neilson, Alice; Schallenberg, Marc
ABSTRACT: Community participation is increasingly embedded into environmental policy with the aim of accelerating transformative change towards sustainable management. A common approach to engaging with communities is through key stakeholders, who are still often selected ad hoc based on their activities. We tested an analytical approach for identifying distinct groups of community preferences as part of a case study to develop a community-led management plan for Blueskin Bay estuary and its catchment. We interviewed 36 community members to elicit their preferences for predefined management objectives following a standardised protocol. Using an agglomerative hierarchical analysis, we determined value-preference clusters for high-level management objectives and more specific objectives. At both levels combined, preference clusters were attributed to some of the commercial interests, such as cockle harvesting, forestry or tourism, which we also identified ad hoc based on their activities in the Blueskin Bay area. However, in addition, cluster analyses revealed five additional preference types: Urban Development Advocates, Cultural Environmentalists, Economic Environmentalists, Integrative Thinkers and those with Diverse Interests. We conclude that cluster analysis more objectively and specifically maps community preferences and, consequently, increases the robustness of collaborative environmental management processes, such as the one underway for Blueskin Bay estuary.